2009
DOI: 10.1111/j.1467-839x.2008.01268.x
|View full text |Cite
|
Sign up to set email alerts
|

Existential function of babies: Babies as a buffer of death‐related anxiety

Abstract: The present study examined babies as death anxiety buffers with Chinese participants in three experiments. In Experiment 1, death-related thoughts increased college-aged participants' interest in human babies. In Experiment 2, images of newborn animals reduced the number of death-related thoughts recorded by college-aged participants. In Experiment 3, female factory workers who read news articles describing deaths of babies had pessimistic estimations of their own life expectancies. An explanation of these res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 18 publications
2
34
0
1
Order By: Relevance
“…They also found that terminally ill hospital patients showed greater preferences for family members under 5 years (versus older family members) in comparison with a non-terminally ill patient group. Follow-up work by Zhou et al [41] showed that students instructed to think about death preferred pictures of young children and viewed them longer than pictures of adults or objects.…”
Section: ( P) Mortality Risk and Saliencementioning
confidence: 99%
See 4 more Smart Citations
“…They also found that terminally ill hospital patients showed greater preferences for family members under 5 years (versus older family members) in comparison with a non-terminally ill patient group. Follow-up work by Zhou et al [41] showed that students instructed to think about death preferred pictures of young children and viewed them longer than pictures of adults or objects.…”
Section: ( P) Mortality Risk and Saliencementioning
confidence: 99%
“…We found no examples of primes being used in traditional societies to study reproductive behaviour. We found that priming was used to investigate influences on sexual and non-sexual risk taking [43,53,54], mate choice [39,40,46,56], fertility intentions and interest in children [6,38,41,45,[57][58][59][60], and parental investment preferences [39,42,55]. Participants were primed through a variety of means, including: reading texts [40,45,46,54,56], word completion tasks ( [6,41], photos [43,46], thought experiments [42,57,59,60], memory essays [53,55] and preceding questions [38,39,58] (see § §5a,c-e, 6b,c,e,j-l,o,p).…”
Section: (Ii) Primingmentioning
confidence: 99%
See 3 more Smart Citations